EFFECTIVENESS OF DIFFERENTIATION EFEKTIVITAS PEMBELAJARAN BERDIFERENSIASI TERHADAP KETERAMPILAN SOSIAL SISWA KELAS IV MATA PELAJARAN IPAS - Lestari, Siska; Arafat, Yasir; Murjainah, Murjainah (Jurnal keilmuan dan Kependidikan dasar, 2023)
This research aims to determine the effectiveness of differentiated learning on the social skills of class IV students in science subjects at SDN 19 Kelapa. The population in this study were 21 class IV students. The sample in this study amounted to 21 people. The sampling technique in this research was using a saturated sampling technique. The method used in this research is an experimental method in the form of Pre-Experimental Designs with the One-Group Pretest-Posttest Design type. Data collection was obtained using activity, observation and documentation rubrics. The data analysis techniques used in this research are normality testing and hypothesis testing. The results of the data analysis data calculations obtained an average posttest result value of 81 (good) in the category "Very Effective. Based on the results of the normality test analysis using the Shapiro-Wilk test with the results of the pretest normality test calculations, it can be obtained that the pretest value is 0.087 > 0.05 and the posttest value is 0.148 > 0.05, so it can be concluded that the data is normally distributed. Meanwhile, the results of the hypothesis test analysis used the Paired-sample-t-test with the hypothesis results contained in Sig (2 tailed) that between the pretest and posttest had a value of 0.00 <0.05. This shows that Ho is rejected and Ha is accepted, meaning that there is effectiveness of differentiated learning on the social skills of class IV students in science subjects at SDN 19 Kelapa. This research needs to be developed by further researchers in subjects other than Natural Sciences such as PPKN, Indonesian, Mathematics so that innovation and novelty can be found related to differentiated learning for students' social skills in the learning process.